Towards a Carbon-Neutral State: International Progress, National Risks, and Coping Strategies (International Journal of Scientific Research and Management (IJSRM), 2021)
Climate change is a major social, economic and environmental challenge facing all countries in the world today. It has increasingly become a priority on the agenda of international relations. This article outlines major developments in international climate action during and after the pandemic. The article identifies the global trends of carbon action on the countries’ agendas for sustainable development in the near future, including accelerate the implementation of mature zero-carbon solutions and promote zero-carbon technology. It then presents risks in tackling the global climate crisis collectively confronted by the international community at present, such as economic slowdown, energy security, carbon financing, price inflation, carbon barrier, carbon trading and carbon debt. With these common dilemmas in mind, the article sums up by proposing multiple possible directions towards reducing emissions and putting forward some community strategies for New Zealand to implement. These include promote the electrification of transportation and establish green infrastructure, consumption, financial, technology and industrial systems. This article aims to inform on the debate about current challenges in building a sustainable and resilient carbon-neutral state in the wake of global public crisis by analyzing global developing trends in addressing climate change, as well as to provoke thinking on potential options for government to enable net zero carbon and new energy future.